(untitled) (Research, Society and Development, 2022)
Eating disorders are considered as a set of clinical conditions, whose main characteristic is the ingestion of unhealthy foods and the attitude of patients towards it, leading to a deterioration of the mental and physical condition. It was defined as the general objective of this study to identify the contributions of nutritionists in eating disorders in different types of eating disorders. This is a systematic review based on bibliographic research, with an exploratory objective in studies published between 2016 and 2022, in the Scielo, LILACS and CAPES databases, and for data analysis, the inductive method and qualitative approach are used. The research results indicate that the constant mental and emotional preoccupation with the subject of food and a troubled relationship with food and with the body itself are central points of an eating disorder. These issues play an important role in life, they can result in a serious psychosomatic illness: an eating disorder. It is concluded that the prevalence of eating disorders has increased and a clinically significant nutritional diagnosis is necessary, since nutritionists are able to assess and advise on the clinical aspects of malnutrition as a key member of the multidisciplinary team. Diet is a central focus in the treatment of eating disorder, suggesting that nutritional care needs to be addressed by a nutritionist alongside the psychological aspects of care that are addressed by a mental health professional.